A note on bonus scales - Centeno, M. de Lourdes (2022)
We revisit the optimal bonus scales introduced by Norberg (Norberg, R., 1976, Scandinavian Actuarial Journal (2): 92-107), Borgan, Hoem, and Norberg (Borgan, O., J. Hoem, and R. Norberg, 1981, Scandinavian Actuarial Journal (2): 165-178), and Gilde and Sundt (Gilde, V., and B. Sundt, 1989, Scandinavian Actuarial Journal (1): 13-22) and underline some potential problems of the linear scales. As a possible solution we propose the use of geometric scales..